Comparison of three low-cost techniques to control fogging of sealed eyewear in a simulated operating room environment: A preliminary analysis - Kumar, Arvind (J Clin Orthop Trauma, 2020)
PURPOSE: In the current COVID pandemic, hermetically sealed eyewear is recommended for safe surgical practices to prevent eye contact with contaminated airborne particles or aerosols. These sealed eyewears definitely reduce the risk of contamination of eyes. However, there is a constant issue of fogging up of the inner surface that prevents good surgical visibility which can impair surgeons’ performance and their ability to perform fine tasks, especially in operating rooms with temperature and humidity controlled as per the COVID guidelines. We investigated the effectiveness of surface-modified anti-fog polyethylene terephthalate(PET) films and the application of a detergent-based surfactant liquid, applied to the inner aspect of viewing frame, and addition of filtered vents in the prevention of fogging up of the protective eyewears in a simulated operating room environment. METHODS: Ten volunteer orthopedic surgeons tested three modifications of a poly-hydrocarbon based hermetically sealed eyewear as a) application of a surface-modified anti-fog PET film on the inner aspect of eyewear, b) application of a detergent-based surfactant coating on the inner aspect of the protective eyewear, and c) addition of two filtered vents/holes on each side of the protective eyewear, covered with an N95 mask cutting. The testing was performed while completing a synthetic bone-based surgical task in a simulated operating room environment of 24–26° temperature and humidity between 40 and 70%, for a maximum of 2 h. The duration to the loss of clear visibility (ability to read a newspaper) and workable visibility (ability to perform the surgical task) was recorded for each volunteer. RESULTS: The detergent-based surfactant provided the longest duration of clear visibility (69.3 ± 8.16 min) and the workable visibility was maintained for more than 2 h. The second best durations of clear visibility (31.9 ± 3.75 min) and workable visibility (41.6 ± 5.39 min) were provided by the surface-modified anti-fog PET film. The addition of the filtered vents provided only a marginal improvement in the visibility. CONCLUSION: A detergent-based surfactant coating of the viewing surface provides a simple, inexpensive and effective solution to the problem of fogging of the protective eyewears. Besides this, the workable vision is maintained for a prolonged duration.